1982
DOI: 10.1002/bjs.1800690104
|View full text |Cite
|
Sign up to set email alerts
|

Late results of proximal gastric vagotomy without drainage for duodenal ulcer: 5–9-year follow-up

Abstract: From 1970 to 1974 proximal gastric vagotomy without drainage was performed in 158 patients for duodenal ulcer. One patient died, giving an operative mortality of 0.6 per cent. Nine unrelated deaths occurred during the period of survey and 5 other patients were lost to follow-up. The remaining 143 patients were followed-up for a minimum of 5 years and a maximum of 9 years. The most frequent symptoms were epigastric fullness and intolerance to milk. Early dumping, detected in 6.7 per cent of the patients, was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Only one study [14] showed a high recurrence rate of 23% eight years after operation. Compared to long-term results of proximal gastric vagotomy for duodenal ulcer (Table 3), similar recurrence rates are noted [4,[16][17][18][19][20][21][22][23][24][25].…”
Section: Recurrent Peptic Ulcer After Pgv With Ulcer Excisionmentioning
confidence: 79%
“…Only one study [14] showed a high recurrence rate of 23% eight years after operation. Compared to long-term results of proximal gastric vagotomy for duodenal ulcer (Table 3), similar recurrence rates are noted [4,[16][17][18][19][20][21][22][23][24][25].…”
Section: Recurrent Peptic Ulcer After Pgv With Ulcer Excisionmentioning
confidence: 79%
“…At the present time, parietal cell vagotomy, or proximal gastric vagotomy (PGV), has become an accepted operative method of treating intractable ulcer disease [21]. The operative techniques of PGV have been well described [19] and the results when compared with vagotomy and antrectomy (the most effective anti-ulcer operative technique) have demonstrated a markedly lower postoperative morbidity and mortality but a higher ulcer recurrence rate-approximately 10% [10,27]. This recurrence rate has been disputed, however, since recent studies have shown that with Congo red confirmation staining of the gastric mucosa intraoperatively, the recurrence rate was comparable to vagotomy and antrectomy (1-2%) [11,42].…”
Section: Discussionmentioning
confidence: 99%
“…Facing the Visick pattern after a given operative procedure, we unconsciously compare it to a healthy population for which we tacitly assume a 100% Visick grade 1 composition. However, results of proximal gastric vagotomy (PGV) without drainage, a procedure praised for its low long-term morbidity and lack of functional sequelae, show an intriguing proportion of symptomatic patients (up to 40% Visick grades 2 to 4) [2][3][4][5][6]. On the other hand, some authors claim a perfect result (Visick 1) in 86% after PGV [7] or even 95% after partial gastrectomy [8].…”
mentioning
confidence: 99%